Effects of molding on property of thermally conductive and electrically insulating polyamide 6–based composite. (September 2019) - Yang, Xuping; Yang, Wenbin; Fan, Jinghui; Wu, Juying; Zhang, Kai
Thermally conductive and electrically insulating polyamide 6 (PA6) matrix quaternary composites were prepared by hot press molding and injection molding, respectively. The quaternary composites were composed of zero-dimensional aluminum oxide particle, one-dimensional silicon carbide whisker, two-dimensional flake graphite, and PA6 resin matrix. Morphology, structure, density, thermal conductivity, volume electrical resistivity, and tensile strength of two types of composites were characterized by scanning electron microscopy, X-ray diffractometer, thermal conductivity tester, high resistance micro-current tester, and tensile tester. The results showed that crystallinity, thermal conductivity, density, and tensile strength of hot press molding samples were superior to those of samples made by injection molding method. This is due to that hot press molding method can provide higher molding pressure and longer annealing time than injection molding. The mechanism could be explained that the performances of the composites were promoted by increasing molding pressure and annealing time.